Optimization of Digital Accounting Transformation in Village-Owned Enterprises Using a Value Chain Perspective for Good Village Governance - Annisa Fatimah; Hesti Wahyuni; Anna Isrowiyah; Widi Dwi Ernawati (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2025)
This study examines how accounting practices in Village-Owned Enterprises (BUMDes) transform from manual bookkeeping to digital systems using a value-chain perspective. It addresses the core problem of misalignment between the formal logic of accounting applications and the cash-flow-based working logic of BUMDes operators, which leads to hybrid adoption, partial use of the system, and continued reliance on manual records that weaken accountability and decision making. A qualitative exploratory case-study design was applied in two BUMDes in East Java, using interviews, observations, document analysis, and focus group discussions analyzed through a value-chain framework. The findings show that digital applications are positioned mainly at the downstream reporting stage, while upstream transaction capture and processing remain manual, making hybrid adoption and workflow–system misalignment a structurally stable pattern shaped by cognitive, capability, and infrastructural constraints. The study proposes a value-chain-based, user-driven transformation model using a Minimum Viable Product (MVP) that accepts simple cash inputs, automates journal mapping, and produces contextual, offline-friendly reports, contributing to the discourse on human–system fit in rural digital transformation and offering practical guidance for BUMDes-oriented accounting system design.